The effect of technology, social media and knowledge shared between gen x'ers and gen y towards effective communication at Pejabat Daerah Dan Tanah Temerloh / Norshawanie Mat Akil - Mat Akil, Norshawanie (Faculty of Business & Management, 2017)
The purpose of this studies is to find out the relationship between technology, social media and knowledge shared between Gen X'ers and Gen Y toward effective communication. This studies was conducted at Pejabat Daerah dan Tanah Temerloh (PDT). The sample size of this studies only 100 out of 181 employees. This studies employed correlation, multiple regression, independent sample t-test and descriptive statistic analysis. Based on the findings in chapter 4,there are significant relationship between technology, social media and knowledge shared toward effective ccommunication and the researcher found that, Gen X'ers are more effective in communication compare to the Gen Y at PDT. As a conclusion, some recommendations have been suggested in order to improve employees effective communication in future.